RESEARCH AND ANALYSIS OF COMBINED ENERGY⁃ABSORBING STRUCTURE FOR FRONT END OF METRO VEHICLES - SU Qiang; WANG XuDong; ZHANG Jie; LIU Kai; XING SongLing (Jixie qiangdu)
A new type of front⁃end energy⁃absorbing structure for metro vehicles was introduced.The mature energy⁃absorbing components and the combined energy⁃absorbing structure were modularized,and the dynamic collision simulation was carried out by using the finite element software,the impact shape of the front⁃end energy⁃absorbing structure was simulated,the process of energy⁃absorbing was analyzed,and the values of vehicle impact interface force,vehicle body deformation and energy⁃absorbing were calculated.Finally,the deformation and energy⁃absorbing stability of the front⁃end energy⁃absorbing structure of vehicles were verified by the test.The test and simulation results match and can meet the requirements of the vehicle collision standard.